THE INFLUENCE OF BEHAVIORAL PSYCHOLOGY ON FINANCIAL DECISIONS OF CONSUMERS IN THE BANKING SECTOR - NIOATA (CHIREAC) ROXANA-MIHAELA; BĂRBĂCIORU IULIANA CARMEN; FILIP ROBERT DORIN (Analele Universităţii Constantin Brâncuşi din Târgu Jiu : Seria Economie)
The main objective of this paper is to analyze how the principles of behavioral psychology influence the financial choices of consumers in the banking sector. In this study, we aim to explore and highlight the impact of various cognitive biases, emotional affect and other psychological factors on financial decisions, particularly in the context of consumers' interaction with financial institutions. Through this analysis, we will pursue a deeper understanding of the decision-making process in relation to key banking products, bank loans, savings and investments, and how these may be shaped by non-rational psychological factors. At the same time, the paper aims to address a number of fundamental questions, such as "How will cognitive biases, the anchoring effect or risk aversion, influence our and consumers' financial choices?" or "To what extent will the application of nudge techniques in the banking sector influence or encourage financial choices to be more rational or beneficial for consumers?".